Pengaruh Circuit Games Terhadap Peningkatan Kerjasama Tim pada Atlet Karate Majenang - Rachmawan, Rizki Aditya; Rezha, Mohamad; Kurniawan, Asep Ridwan; Kardani, Gani (Jurnal Keolahragaan, 2023)
The research to be carried out has a goal by the formulation of the problem set, namely "To find out whether the outdoor education circuit games can have a significant influence on increasing the teamwork of Majenang karate athletes". In this study, the author used experimental research methods to determine the effect of circuit games on increasing teamwork in Majenang karate athletes. This study used a population of Majenang karate athletes with a population of 20 people in the age group of 14-16 years. The sample used by the age group of 14-16 years was selected which was suitable to be used as a research sample of 20 people. The results of the identification of problems show that Majenang Karate athletes tend to be individual and lack teamwork development. One of the factors that cause such individual characteristics is that the majority of match numbers that are followed are individual numbers. However, research shows that the use of circuit games in Majenang Regency Karate training has a significant effect on improving teamwork. This is proven by the increase in teamwork that occurs in a shorter time. Therefore, the use of circuit games has a positive impact on increasing teamwork and providing various benefits for Majenang Karate athletes.